2020
DOI: 10.1177/0963662520952999
|View full text |Cite
|
Sign up to set email alerts
|

‘Will polar bears melt?’ A qualitative analysis of children’s questions about climate change

Abstract: Climate change poses a grave threat to future generations, yet relatively little research examines children’s understandings of the issue. This study examines the questions children ask about climate change – rather than their answers to adults’ questions – exploring whether their questions suggest they view climate change as psychologically proximal or distant. Children aged 10–12 from 14 UK schools took part in an online event, asking scientists questions in a ‘climate zone’. The questions were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Many argue that high levels of worry about climate change arise from a perception that climate change threatens one's object of care (53). For some, worry about global environmental problems, including climate change, is a kind of macro worry, with moral/ethical undertones, where people do not primarily worry about themselves and loved ones but rather think about more distant aspects such as people living in faraway countries, animals and nature, and future generations (54,55). This kind of macro worry and thinking is most common among people with strong universal and biospheric values, that is, people who value highly global justice, peace, equality, and the well-being of nature and animals (38,48,56).…”
Section: Preconditions Of Eco-anxiety and Climate Change Worrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many argue that high levels of worry about climate change arise from a perception that climate change threatens one's object of care (53). For some, worry about global environmental problems, including climate change, is a kind of macro worry, with moral/ethical undertones, where people do not primarily worry about themselves and loved ones but rather think about more distant aspects such as people living in faraway countries, animals and nature, and future generations (54,55). This kind of macro worry and thinking is most common among people with strong universal and biospheric values, that is, people who value highly global justice, peace, equality, and the well-being of nature and animals (38,48,56).…”
Section: Preconditions Of Eco-anxiety and Climate Change Worrymentioning
confidence: 99%
“…If we turn to children and adolescents, some scholars argue that it could be more difficult for this group to deal with climate change worry given developmental factors and the fact that young people have even less control over this issue than adults (see 16,42). Many studies performed in different countries have found that young people have a rather dark picture of the global future, not least in relation to climate change and other global environmental problems, with dystopic and science fiction-inspired imageries (55,60,(93)(94)(95)(96)(97). However, these dark views are often not related to views of young people's own personal futures (94,97), suggesting that climate change is still a distant macro worry for some young people.…”
Section: Negative Emotions About Global Environmental Problems and Relations To Mental Health Worry Anxiety Hopelessness And Relations Tomentioning
confidence: 99%
“…Prior research shows that children's understanding of climate change is often limited, erroneous, and largely influenced by the media (Rousell & Cutter-Mackenzie-Knowles, 2020). A considerable body of research that examined older children's and adults' understanding of climate change shows that they hold misconceptions about climate change and the ozone layer (Jarrett & Takacs, 2020), limited knowledge of the climate system (Schauss & Sprenger, 2021), and uncertainties about climate change (Adams, 2001) and its future impacts (Lee & Barnett, 2020). Emerging evidence also suggests that older children find it difficult to conceptualise climate change (Jorgenson et al, 2019).…”
Section: Climate Literacy In Early Childhoodmentioning
confidence: 99%
“…Two studies analysed participants' free-form writing when asked to produce 10 statements about climate change (de Guttry et al, 2017) or, in a study with children, to pose questions about climate change to an expert panel (K. Lee & Barnett, 2020). In both studies, PD was a prevalent concept that was voluntarily mentioned, with many participants feeling very distant from climate change.…”
Section: Qualitative Studies and Text Analysismentioning
confidence: 99%
“…Keller et al to most often, followed by temporal and social distance (de Guttry et al, 2017). The children's questions emphasised how interlinked the dimensions were (K. Lee & Barnett, 2020), with temporally current climate-change impacts being seen as spatially further away than future impacts. This is a departure from the classic assumptions of CLT, which states that dimensions are positively correlated, where temporally close impacts are thought to be spatially close.…”
Section: Qualitative Studies and Text Analysismentioning
confidence: 99%